BERNSTEIN, Richard J. (2021): Encuentros pragmáticos. Traducción de Alejandro Sánchez Lopera. Barcelona: Gedisa. - Pérez del Amo, M.ª de los Ángeles (Daimon Revista Internacional de Filosofia, 2023)
Reseña de: BERNSTEIN, Richard J. (2021): Encuentros pragmáticos. Traducción de Alejandro Sánchez Lopera. Barcelona: Gedisa.